The mobile tax bill: how mobile is impacted by sector-specific taxes - Pau Castells; Xavier Pedrós; Mayuran Sivakumaran (International Telecommunications Society (ITS), 2019)
Many developing countries have introduced sector-specific taxes on the consumption of mobile services, which apply on top of general taxes, and therefore discourage the positive externalities that have been estimated to be associated with the use of mobile technology on workers' productivity and consumer welfare. This paper investigates the first order impact of these taxes on consumer prices. Firstly, we develop a measure of prices of mobile services and devices, and create a framework to calculate prices before and after tax, taking into account both general and sector-specific taxes, for more than 100 markets worldwide. We use this to provide country and regional benchmarks and to run preliminary bivariate analyses on how taxes impact prices; and how both of these relate to mobile connectivity outcomes. This provides updated analysis, as of 2017 - making a contribution to previous studies (e.g., ITU 2013). Secondly, we provide the results of a tracker of sector-specific tax changes, from 2011 to 2018, for over 100 markets - providing insights on how fiscal policies have changed in their treatment of mobile services and devices in latest years.
Keywords: L96; H20; 330